Entrepreneurship support institutions in Russia - N. A. Krasovskiy (Publishing House of the State University of Management, 2021)
The article presents historical and modern aspects of the theory of entrepreneurship, the role of entrepreneurship in the socio-economic life of the country. The paper considers the reasons: why the state should create conditions for the development of small and medium-sized businesses. The study gives criteria for defining small and medium-sized businesses in Russia and in the European Union. The author studies and presents the main indicators that characterize the degree of development of small and medium-sized businesses in terms of their involvement in the economy. The article gives the classification of the main measures to support small and medium-sized businesses in countries with a developed business sector. The paper considers the main measures of state support for entrepreneurship in Russia and assesses their effectiveness.